Presupposition in Film Discourse: A Systematic Literature Review of Pragmatic Analyses - Elfrida, Rotua (Lembaga Riset Mutiara Akbar, 2025)
This article presents a systematic literature review (SLR) of 20 scholarly studies published between 2020 and 2024 that investigate presupposition in film discourse from a pragmatic lens. The review aims to synthesize dominant presupposition types, theoretical frameworks, pragmatic functions, and genre-specific trends within cinematic language. Existential, factive, and lexical presuppositions are the most frequently employed, shaping character development, narrative cohesion, and cultural framing. Yule’s (1996) typology remains the predominant analytical framework, while animated and dramatic films emerge as the most analyzed genres due to their pedagogical and sociocultural richness. The findings emphasize the role of presupposition as a discourse strategy that conveys implicit meaning and ideological nuance, supporting audience interpretation without explicit exposition. Furthermore, several studies highlight its application in ESL/EFL classrooms to enhance pragmatic competence. Despite the growth in this research area, gaps persist in multimodal analysis and cross-cultural comparisons. This review not only consolidates key insights but also calls for more integrative approaches that consider visual, verbal, and cultural dimensions of cinematic texts. It contributes to advancing pragmatic inquiry and encourages further exploration of presupposition as a dynamic tool in media discourse.